In Search of the Supracultural: American Missionaries in the Gulf in 1920s-1930s - Zdanowski, Jerzy (Islam and Christian-Muslim relations, 2019)
This article examines the dynamics of cultural encounters, with reference to the concept of Gustav Warneck (1834-1910) of the connections between mission and culture. It introduces the reader to the personal experience of the missionaries of the Arabian Mission, which was launched in 1889 and operated until 1973 in Basra, Amara, Bahrain, Kuwait and Muscat. While the Mission did not bring about the mass conversion of Muslims, its activities resulted in numerous everyday contacts with the local population. The article stresses that missionaries were a diverse group of individuals with different methods and aspirations, and explores how these diversities challenge a narrative on missions that usually reduces them to a homogenized missiology. Much of the content focuses on the 1920s-1930s, a very unique period in the Middle East, and seeks to show the way that the historical and local context shaped the diversities of missiology. Findings suggest that missionaries, as outsiders in the process of contacting the alien culture, often crossed cultural borders, and that these cultural encounters exhibited contrasting dynamics: the exclusion and rejection of local culture was accompanied by the discovery' of Islam and the search for supracultural' components of Islamic culture.